Endonuclease G interacts with histone H2B and DNA topoisomerase II alpha during apoptosis - Vařecha, Miroslav; Potěšilová, Michaela; Matula, Pavel; Kozubek, Michal (Molecular and cellular biochemistry, 2012)
Apoptosis is a natural form of cell death involved in many physiological changes in the cell. Defects in the process of apoptosis can lead to serious diseases. During some apoptotic pathways, proteins apoptosis-inducing factor (AIF) and endonuclease G (EndoG) are released from the mitochondria and they translocate into the cell nuclei, where they probably participate in chromatin degradation together with other nuclear proteins. Exact mechanism of EndoG activity in cell nucleus is still unknown. Some interacting partners like flap endonuclease 1, DNase I, and exonuclease III were already suggested, but also other interacting partners were proposed. We conducted a living-cell confocal fluorescence microscopy followed by an image analysis of fluorescence resonance energy transfer to analyze the possibility of protein interactions of EndoG with histone H2B and human DNA topoisomerase II alpha (TOPO2a). Our results show that EndoG interacts with both these proteins during apoptotic cell death. Therefore, we can conclude that EndoG and TOPO2a may actively participate in apoptotic chromatin degradation. The possible existence of a degradation complex consisting of EndoG and TOPO2a and possibly other proteins like AIF and cyclophilin A have yet to be investigated.
Keywords: rezonanční přenos fluorescenční energie; Protein Interaction Mapping; DNA-topoisomerasy typu II; antigeny nádorové; časové faktory; restrukturace chromatinu; apoptóza; Endodeoxyribonucleases; lidé; Microscopy, Confocal; Protein Interaction Domains and Motifs; Recombinant Fusion Proteins; Humans; Chromatin Assembly and Disassembly; mapování interakce mezi proteiny; endodeoxyribonukleasy; Fluorescence Resonance Energy Transfer; interakční proteinové domény a motivy; Histones; molekulární modely; Antigens, Neoplasm; DNA Topoisomerases, Type II; Apoptosis; Cell Nucleus; DNA-Binding Proteins; Protein Conformation; Time Factors; HeLa buňky; rekombinantní fúzní proteiny; Transfection; konformace proteinů; konfokální mikroskopie; HeLa Cells; buněčné jádro; histony; transfekce; DNA vazebné proteiny; Models, Molecular